Formulasi salep sari batang daun talas (Colocasia esculenta L. ) schoot pada penyembuhan luka sayat pada tikus putih jantan (Rattus norvegicus) - Ardiani, Rani; Shufyani, Fahma; Siregar, Syati Manaharawan; Silalahi , Ali Affan (Journal of Pharmaceutical and Sciences, 2025)
Introduction: Taro contains several compounds that can accelerate wound healing, such as flavonoids, phenols, and saponins. These compounds act as natural antibiotics, cleansing wounds with their antibacterial and antifungal properties. Therefore, this plant can aid in the wound healing process. Tannins, on the other hand, have the ability to constrict blood vessels and reduce bleeding in the wound area, decrease infection, and aid in wound healing during the inflammatory phase. One of the wound healing factors, vitamin C helps strengthen the walls of blood vessels, especially in the injured area, to maintain blood supply there and assist in accelerating collagen synthesis during the wound healing process. Lectin, a substance that can accelerate wound closure by aiding better cell regeneration. Arecaceae plants have many benefits for society, such as being used as a food source by harvesting their tubers, or being used as ornamental plants that beautify yards. Taro is also used as medicine both internally and externally. Almost all parts of the taro plant are processed into medicines, and the tubers, stem bark, and roots are crushed and then applied to the skin to heal wounds or bruises. Objective: This study aims to determine the wound healing effects of the sap from the taro stem (Colocasia esculenta L) Schott on male rats (Rattus norvegicus). Method: This study uses an experimental method, which includes sampling, preparation of taro leaf stem extract with concentrations of 2%, 4%, 6%, ointment evaluation test, and incision wound healing activity test on white rats grouped into 5 groups, each consisting of 3 rats. Statistical analysis includes one-way ANOVA to see if there is a significant difference between concentrations in the healing of incisional wounds in male white rats. Result: The research conducted shows that F1 (2% concentration) can heal the rats on the 10th day. F2 (4% concentration) the rats healed on the 8th day, F3 (6% concentration) the cut wounds healed on the 7th day, positive control (Betadine ointment) all rats healed on the 7th day. Conclusion: The extract of taro leaf stems (Colocasia esculenta L) Schoot can be formulated into an ointment preparation for the healing of incised wounds in male white rats (Rattus norvegicus), with the most effective concentration being 6% because it can heal incised wounds the fastest among the other concentrations.